A combined network control approach for the edge cloud and LPWAN‐based IoT services. (21st December 2017) - Kim, Dae‐Young; Kim, Seokhoon; Park, Jong Hyuk
Summary: Recently, low‐power wide area network (LPWAN) has attracted attention as a wireless network for long‐range Internet of Things (IoT) services. IoT devices in an LPWAN are managed by a network server in the cloud. Various data are delivered from the IoT devices to the network server, and the role of the centralized network server in the cloud has become important for efficient data transfer over an LPWAN. However, control by the network server concentrates the control load on the network server and is vulnerable in terms of response time and bandwidth utilization. Therefore, this paper takes the approach of moving the control of the LPWAN to the edge cloud, which provides computing and storage environments at base stations. An LPWAN gateway is then integrated with the edge cloud, and LPWAN data are cached at the edge cloud in the gateway for LPWAN control. LPWAN control such as report interval control for data, transmission power control, and data aggregation is applied to improve the efficiency of data transmission. Network control is performed by learning using cached data in the edge cloud. Compared with the existing LPWAN control approach, the proposed approach exhibits improved performance for IoT data transmission. The simulation results show the proposed approach's efficiency.